Desenvolvimento da alface hidropônica com complemento de luz vermelha em sistema fotovoltaico - Guerreiro, Daniela Teixeira (2021)
Lettuce (Lactuca sativa L.) is the main leafy and most cultivated vegetable in the world, being of the curly type with light green leaves and the smooth one with bright green leaves. This work aimed to evaluate the growth behavior of lettuce, grown in hydroponics submitted to complementary red lighting during the day, installed inside the shade cover under poorly controlled climatic conditions, testing two treatments (red light in the 660 nm range) and natural light) in 3 repetitions and two varieties (Vera and Regiane), kept accessible during daytime from 8:00 am to 6:00 pm, at 0.40 m height of the seedlings, where, it was supported by solar energy (photovoltaic). The seedlings were previously cultivated by a nursery in the region, until they reached the age of 15 days after germination, from the 16th day onwards, the seedlings were transferred to the vertical Hydroponics system in NFT system (Nutrient Film Technique), which was also maintained by solar energy. Thus, the plants with natural lighting and complementary red lighting were analyzed until completing 32 days in the NFT system, where the plants were evaluated in: number of leaves (NF), height of the final plant (APF), root length (CR), stem length (CC), stem diameter (DC), green plant mass (MVP), green root mass (MVR), green stem mass (MVC), dry plant mass (MSP), dry mass of the root (MSR), dry mass of the stem (MSC). It was found that for almost all the characteristics analyzed, there was a greater growth in the treatment with red LED lighting, in particular the (NF) in the curly lettuce with 68.87% and in the plain lettuce the (DC) with 75.24 %. The only characteristic that had a better result in the cultivation of lettuce with natural light was in the culture of smooth lettuce in (CC). The treatment with red LED light obtained a higher production efficiency in the cultivation of hydroponic lettuce in relation to the treatment with natural light.